Tumor Suppressor p16INK4A Regulates Polycomb-mediated DNA Hypermethylation in Human Mammary Epithelial Cells - Paul A. Reynolds; Mahvash Sigaroudinia; Giuseppe Zardo; Matthew B. Wilson; Geoffrey Marsing Benton; Caroline Miller; Chibo Hong; Jane Fridlyand; J Costello; Thea D. Tlsty (2006)
Alterations in DNA methylation are important in cancer, but the acquisition of these alterations is poorly understood. Using an unbiased global screen for CpG island methylation events, we have identified a non-random pattern of DNA hypermethylation acquired in p16-repressed cells. Interestingly, this pattern included loci located upstream of a number of homeobox genes. Upon removal of p16INK4A activity in primary human mammary epithelial cells, polycomb repressors, EZH2 and SUZ12, are up-regulated and recruited to HOXA9, a locus expressed during normal breast development and epigenetically silenced in breast cancer. We demonstrate that at this targeted locus, the up-regulation of polycomb repressors is accompanied by the recruitment of DNA methyltransferases and the hypermethylation of DNA, an endpoint, which we show to be dependent on SUZ12 expression. These results demonstrate a causal role of p16INK4A disruption in modulating DNA hypermethylation, and identify a dynamic and active process whereby epigenetic modulation of gene expression is activated as an early event in breast tumor progression. Alterations in DNA methylation are important in cancer, but the acquisition of these alterations is poorly understood. Using an unbiased global screen for CpG island methylation events, we have identified a non-random pattern of DNA hypermethylation acquired in p16-repressed cells. Interestingly, this pattern included loci located upstream of a number of homeobox genes. Upon removal of p16INK4A activity in primary human mammary epithelial cells, polycomb repressors, EZH2 and SUZ12, are up-regulated and recruited to HOXA9, a locus expressed during normal breast development and epigenetically silenced in breast cancer. We demonstrate that at this targeted locus, the up-regulation of polycomb repressors is accompanied by the recruitment of DNA methyltransferases and the hypermethylation of DNA, an endpoint, which we show to be dependent on SUZ12 expression. These results demonstrate a causal role of p16INK4A disruption in modulating DNA hypermethylation, and identify a dynamic and active process whereby epigenetic modulation of gene expression is activated as an early event in breast tumor progression. Aberrant epigenetic changes have been documented in cancer, which act as alternatives to mutation or deletion to disrupt tumor suppressor gene function (1Feinberg A.P. Tycko B. Nat. Rev. Cancer. 2004; 4: 143-153Crossref PubMed Scopus (1797) Google Scholar, 2Herman J.G. Baylin S.B. N. Engl. J. Med. 2003; 349: 2042-2054Crossref PubMed Scopus (2784) Google Scholar, 3Jones P.A. Baylin S.B. Nat. Rev. Genet. 2002; 3: 415-428Crossref PubMed Google Scholar). However, the control of this aberrant epigenetic remodeling is unknown. Both changes in the levels of chromatin remodeling proteins, including polycomb group (PcG) 2The abbreviations used are: PcG, polycomb group; CDK, cyclin-dependent kinase; HMEC, human mammary epithelial cell; HMF, human mammary fibroblast; PD, population doubling; PRC2, polycomb repressor complex 2; RLGS, restriction landmark genomic scanning; RM, reduction mammoplasty; shRNA, small hairpin RNA; vHMEC, variant human mammary epithelial cell; nt, nucleotide. proteins, and genome-wide loss and localized gains in DNA methylation have been reported in many tumors (1Feinberg A.P. Tycko B. Nat. Rev. Cancer. 2004; 4: 143-153Crossref PubMed Scopus (1797) Google Scholar, 2Herman J.G. Baylin S.B. N. Engl. J. Med. 2003; 349: 2042-2054Crossref PubMed Scopus (2784) Google Scholar, 3Jones P.A. Baylin S.B. Nat. Rev. Genet. 2002; 3: 415-428Crossref PubMed Google Scholar). PcG proteins form polycomb repressor complexes (PRCs) to control cell fate determination, stem cell renewal, cell growth, and cell division. The PRC2 complex contains at least four different subunits, EED, EZH2, SUZ12, and AEBP2 (4Cao R. Zhang Y. Mol. Cell. 2004; 15: 57-67Abstract Full Text Full Text PDF PubMed Scopus (629) Google Scholar), many of which are downstream transcriptional targets of E2F in multiple cell types (5Bracken A.P. Pasini D. Capra M. Prosperini E. Colli E. Helin K. EMBO J. 2003; 22: 5323-5335Crossref PubMed Scopus (972) Google Scholar, 6Weinmann A.S. Bartley S.M. Zhang T. Zhang M.Q. Farnham P.J. Mol. Cell. Biol. 2001; 21: 6820-6832Crossref PubMed Scopus (331) Google Scholar). The PRC2-associated PcG proteins, EZH2 and SUZ12, are overexpressed in a wide spectrum of human tumors (7Kleer C.G. Cao Q. Varambally S. Shen R. Ota I. Tomlins S.A. Ghosh D. Sewalt R.G. Otte A.P. Hayes D.F. Sabel M.S. Livant D. Weiss S.J. Rubin M.A. Chinnaiyan A.M. Proc. Natl. Acad. Sci. U. S. A. 2003; 100: 11606-11611Crossref PubMed Scopus (1362) Google Scholar, 8Varambally S. Dhanasekaran S.M. Zhou M. Barrette T.R. Kumar-Sinha C. Sanda M.G. Ghosh D. Pienta K.J. Sewalt R.G. Otte A.P. Rubin M.A. Chinnaiyan A.M. Nature. 2002; 419: 624-629Crossref PubMed Scopus (2206) Google Scholar, 9Kirmizis A. Bartley S.M. Farnham P.J. Mol. Cancer Ther. 2003; 2: 113-121PubMed Google Scholar) and increased EZH2 in cancer cells generates a variant PRC that may alter the targeting of gene silencing (10Kuzmichev A. Margueron R. Vaquero A. Preissner T.S. Scher M. Kirmizis A. Ouyang X. Brockdorff N. Abate-Shen C. Farnham P. Reinberg D. Proc. Natl. Acad. Sci. U. S. A. 2005; 102: 1859-1864Crossref PubMed Scopus (360) Google Scholar). Changes in DNA methylation patterns have been identified in cancer and result in the silencing of important tumor suppressor genes involved in cell cycle regulation, differentiation, apoptosis, DNA repair, and metastasis (1Feinberg A.P. Tycko B. Nat. Rev. Cancer. 2004; 4: 143-153Crossref PubMed Scopus (1797) Google Scholar, 2Herman J.G. Baylin S.B. N. Engl. J. Med. 2003; 349: 2042-2054Crossref PubMed Scopus (2784) Google Scholar, 3Jones P.A. Baylin S.B. Nat. Rev. Genet. 2002; 3: 415-428Crossref PubMed Google Scholar). Recent studies suggest that DNA hypermethylation is the consequence of gene silencing (11Bachman K.E. Park B.H. Rhee I. Rajagopalan H. Herman J.G. Baylin S.B. Kinzler K.W. Vogelstein B. Cancer Cell. 2003; 3: 89-95Abstract Full Text Full Text PDF PubMed Scopus (359) Google Scholar, 12Mutskov V. Felsenfeld G. EMBO J. 2004; 23: 138-149Crossref PubMed Scopus (240) Google Scholar, 13Leu Y.W. Yan P.S. Fan M. Jin V.X. Liu J.C. Curran E.M. Welshons W.V. Wei S.H. Davuluri R.V. Plass C. Nephew K.P. Huang T.H. Cancer Res. 2004; 64: 8184-8192Crossref PubMed Scopus (171) Google Scholar, 14Tamaru H. Selker E.U. Nature. 2001; 414: 277-283Crossref PubMed Scopus (856) Google Scholar, 15Vire E. Brenner C. Deplus R. Blanchon L. Fraga M. Didelot C. Morey L. Van Eynde A. Bernard D. Vanderwinden J.M. Bollen M. Esteller M. Di Croce L. de Launoit Y. Fuks F. Nature. 2006; 439: 871-874Crossref PubMed Scopus (1730) Google Scholar). The product of the INK4A locus, p16, encodes a cyclin-dependent kinase (CDK) inhibitor that functions as a negative regulator of cyclin/CDK complexes. It binds preferentially to CDK4/6 and prevents their association with D-type cyclins, thus inhibiting pRB phosphorylation and progression through the cell cycle (16Rocco J.W. Sidransky D. Exp. Cell Res. 2001; 264: 42-55Crossref PubMed Scopus (399) Google Scholar, 17Sherr C.J. McCormick F. Cancer Cell. 2002; 2: 103-112Abstract Full Text Full Text PDF PubMed Scopus (1315) Google Scholar). Cells with loss of p16INK4A activity exhibit increased E2F activity. In humans, p16INK4A has a role in the maintenance of normal cellular properties, preventing centrosome dysfunction and genomic instability (18McDermott K.M. Zhang J. Holst C.R. Kozakiewicz B.K. Singla V. Tlsty T.D. PLoS Biol. 2006; 4: e51Crossref PubMed Scopus (108) Google Scholar). In human tumors, inactivation of p16INK4A is as an early event (16Rocco J.W. Sidransky D. Exp. Cell Res. 2001; 264: 42-55Crossref PubMed Scopus (399) Google Scholar, 17Sherr C.J. McCormick F. Cancer Cell. 2002; 2: 103-112Abstract Full Text Full Text PDF PubMed Scopus (1315) Google Scholar) and loss of p16/Rb activity occurs through deletion, mutation or hypermethylation of p16INK4A or other members of the pRb pathway in the majority of tumors (17Sherr C.J. McCormick F. Cancer Cell. 2002; 2: 103-112Abstract Full Text Full Text PDF PubMed Scopus (1315) Google Scholar). HOX genes encode DNA binding transcription factors that are spatially and temporally regulated during embryonic development and are critical to the regulation of gene expression, morphogenesis, and differentiation (19Botas J. Curr. Opin. Cell Biol. 1993; 5: 1015-1022Crossref PubMed Scopus (106) Google Scholar). In breast cancer, there are numerous examples of the aberrant repression of HOX genes (20Carrio M. Arderiu G. Myers C. Boudreau N.J. Cancer Res. 2005; 65: 7177-7185Crossref PubMed Scopus (92) Google Scholar, 21Raman V. Martensen S.A. Reisman D. Evron E. Odenwald W.F. Jaffee E. Marks J. Sukumar S. Nature. 2000; 405: 974-978Crossref PubMed Scopus (406) Google Scholar). In contrast to the transforming properties of HOXA9 in lymphocytes, it has been reported that HOXA9 expression is necessary for lactational differentiation (22Chen F. Capecchi M.R. Proc. Natl. Acad. Sci. U. S. A. 1999; 96: 541-546Crossref PubMed Scopus (158) Google Scholar) and is absent in breast cancer (23Unger M.A. Microarray Analysis Identifies HOXA9 as a Novel Breast Cancer Progression Gene. Ph.D. thesis. University of Pennsylvania, 2002Google Scholar). However, the role of HOXA9 in the mammary gland is unclear. Rare foci of morphologically normal epithelial cells with hypermethylation of p16INK4A promoter sequences and loss of p16INK4A activity have been observed in vivo in disease-free tissue from breast (24Holst C.R. Nuovo G.J. Esteller M. Chew K. Baylin S.B. Herman J.G. Tlsty T.D. Cancer Res. 2003; 63: 1596-1601PubMed Google Scholar) and other organs (25Belinsky S.A. Palmisano W.A. Gilliland F.D. Crooks L.A. Divine K.K. Winters S.A. Grimes M.J. Harms H.J. Tellez C.S. Smith T.M. Moots P.P. Lechner J.F. Stidley C.A. Crowell R.E. Cancer Res. 2002; 62: 2370-2377PubMed Google Scholar, 26Wong D.J. Paulson T.G. Prevo L.J. Galipeau P.C. Longton G. Blount P.L. Reid B.J. Cancer Res. 2001; 61: 8284-8289PubMed Google Scholar) and are hypothesized to be precursors to cancer (27Tlsty T.D. Crawford Y.G. Holst C.R. Fordyce C.A. Zhang J. Mc-Dermott K. Kozakiewicz K. Gauthier M.L. J. Mammary Gland Biol. Neoplasia. 2004; 9: 263-274Crossref PubMed Scopus (71) Google Scholar). In the breast, these rare p16INK4A-silenced cells (variant human mammary epithelial cells or vHMEC) can be isolated from breast tissue samples and propagated in culture where they have been shown to exhibit selected pre-neoplastic phenotypes and biomarkers (18McDermott K.M. Zhang J. Holst C.R. Kozakiewicz B.K. Singla V. Tlsty T.D. PLoS Biol. 2006; 4: e51Crossref PubMed Scopus (108) Google Scholar, 24Holst C.R. Nuovo G.J. Esteller M. Chew K. Baylin S.B. Herman J.G. Tlsty T.D. Cancer Res. 2003; 63: 1596-1601PubMed Google Scholar, 28Crawford Y.G. Gauthier M.L. Joubel A. Mantei K. Kozakiewicz K. Afshari C.A. Tlsty T.D. Cancer Cell. 2004; 5: 263-273Abstract Full Text Full Text PDF PubMed Scopus (130) Google Scholar, 29Shim Y.H. Park H.J. Choi M.S. Kim J.S. Kim H. Kim J.J. Jang J.J. Yu E. Mod. Pathol. 2003; 16: 430-436Crossref PubMed Scopus (28) Google Scholar, 30Brenner A.J. Stampfer M.R. Aldaz C.M. Oncogene. 1998; 17: 199-205Crossref PubMed Scopus (229) Google Scholar, 31Foster S.A. Wong D.J. Barrett M.T. Galloway D.A. Mol. Cell. Biol. 1998; 18: 1793-1801Crossref PubMed Scopus (193) Google Scholar, 32Huschtscha L.I. Noble J.R. Neumann A.A. Moy E.L. Barry P. Melki J.R. Clark S.J. Reddel R.R. Cancer Res. 1998; 58: 3508-3512PubMed Google Scholar, 33Romanov S.R. Kozakiewicz B.K. Holst C.R. Stampfer M.R. Haupt L.M. Tlsty T.D. Nature. 2001; 409: 633-637Crossref PubMed Scopus (398) Google Scholar). Expression of these biomarkers are observed in the majority of premalignant lesions (29Shim Y.H. Park H.J. Choi M.S. Kim J.S. Kim H. Kim J.J. Jang J.J. Yu E. Mod. Pathol. 2003; 16: 430-436Crossref PubMed Scopus (28) Google Scholar, 34Gauthier M.L. Pickering C.R. Miller C.J. Fordyce C.A. Chew K.L. Berman H.K. Tlsty T.D. Cancer Res. 2005; 65: 1792-1799Crossref PubMed Scopus (48) Google Scholar), contributing to the evidence that these p16INK4A-silenced cells are early manifestations of malignancy and provide an excellent model system to study early events in cancer formation. In the present study, we show that loss of tumor suppressor p16INK4A activity leads to the up-regulation of polycomb proteins, EZH2 and SUZ12 and DNA hypermethylation. We have identified a non-random pattern of DNA hypermethylation using an unbiased global screen for CpG island methylation events in primary human mammary epithelial cells with loss of p16INK4A activity. We demonstrate that polycomb proteins play a causal role in targeting DNA hypermethylation to the HOXA9 locus. In primary breast tumors, we find HOXA9 is epigenetically silenced. These studies suggest that epigenetic changes, controlled by loss of p16INK4A activity, are some of the earliest events in breast tumor progression. Cell Culture and Plasmids—Isolation and culture of HMEC in modified MCDB 170 (MEGM, Cambrex) has been described (35Hammond S.L. Ham R.G. Stampfer M.R. Proc. Natl. Acad. Sci. U. S. A. 1984; 81: 5435-5439Crossref PubMed Scopus (362) Google Scholar), HMF were grown in RPMI1640 supplemented with 20% fetal bovine serum. We studied HMEC/vHMEC/HMF from reduction mammoplasty specimens from ten individuals: 48 and 240 (kindly provided by Martha Stampfer), RM9, RM13, RM15, RM16, RM18, RM20, RM21, and RM163 (cells derived in our laboratory). vHMEC clones were generated using standard ring cloning procedures. Population doublings (PD) were calculated using the equation PD = log(A/B)/log2, where A is the number of cells collected, and B is the number of cells plated. Cell cycle profiles were analyzed by FACS. pBABE-myc-EZH2 has been described (36Caretti G. Di Padova M. Micales B. Lyons G.E. Sartorelli V. Genes Dev. 2004; 18: 2627-2638Crossref PubMed Scopus (510) Google Scholar). The SUZ12 ORF was excised from pCMV-SUZ12 (a kind gift from Dr. Peggy Farnham) and cloned into pBABE-Hygro. The shRNA specific for p16INK4a encoded inverted repeats of 27 bp corresponding to nt 381-407 of the human CDKN2A p16INK4a cDNA (GenBank™ accession No. NM000077), separated by an 8-nt spacer (37Narita M. Nunez S. Heard E. Lin A.W. Hearn S.A. Spector D.L. Hannon G.J. Lowe S.W. Cell. 2003; 113: 703-716Abstract Full Text Full Text PDF PubMed Scopus (1712) Google Scholar). The shRNA specific for GFP was purchased from Open Biosystems. Constructs were packaged in Phoenix A cells for viral propagation. Retroviral infection of HMEC/vHMEC was carried out using standard methods. Puromycin selection (4 μg/ml) or hygromycin selection (20 μg/ml) was applied 24 h after retroviral infection and continued for 5 d after which cells were harvested. Transient transfection of HMEC with siSUZ12 (SMARTpool M006957) or siControl (D001206) (Dharmacon) was carried out using Lipofectamine (Invitrogen). In siRNA/shRNA combination treatment, retroviral infection was followed 12 h later by siSUZ12 or siControl transfection. Another 24 h later, puromycin selection was applied (4 μg/ml) for 5 d after which time the cells were harvested. In order to induce demethylation, we incubated vHMEC with 5-aza-2′-deoxycytidine (1 μm) and drug-containing media was replaced every 24 h for 3 days. Bisulfite Treatment, PCR Analysis, and Western Blotting—We isolated genomic DNA (Promega) from cells and performed bisulfite treatment basically as described (38Herman J.G. Graff J.R. Myohanen S. Nelkin B.D. Baylin S.B. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 9821-9826Crossref PubMed Scopus (5230) Google Scholar). We digested 2 μg of genomic DNA with EcoRV and then denatured it in 0.3 m NaOH for 20 min at 37 °C. We used an 8-h incubation at 55 °C followed by removal of free bisulfite using a Wizard Clean Up kit (Promega). PCR was performed using primers to amplify region gb/AC004080: 43040-42674 (MR1) or 40432-40134 (HOX promoter). Nested PCR products were cloned into pCR2.1 (Invitrogen) followed by nucleotide sequencing using the Big-Dye Termination method (ABI). Methylation-specific PCR primers to the HOXA9 regulatory region were designed by the MethPrimer program (39Li L.C. Dahiya R. Bioinformatics. 2002; 18: 1427-1431Crossref PubMed Scopus (1988) Google Scholar) and identified methylated or unmethylated alleles (A9MS: 5′-TCGGGGTTAGATAGGGAGTCGGGA-3′, A9MA:5′-AAAATAAAAACGAAAAACAAACGAA-3′, A9US:5′-TTGGGGTTAGATAGGGAGTTGGGA-3′, A9UA:5′-AAAAATAAAAACAAAAAACAAACAAA-3′). Total RNA was isolated from cells and cDNA synthesized using standard methods. Quantitative real-time PCR (TaqMan) was performed on cDNA (40Heid C.A. Stevens J. Livak K.J. Williams P.M. Genome Res. 1996; 6: 986-994Crossref PubMed Scopus (5018) Google Scholar) using the standard curve method with primer/probe sets for HOXA9 (ABI: Hs00365956_m1), p16INK4A (ABI: Hs00233365_m1) SUZ12 (ABI: Hs01093658_m1), EZH2 (ABI: Hs00544830_m1), EED (ABI: Hs00243609_m1), PCNA (ABI: Hs00427214_g1), and for GUSB (ABI: Hs99999908_m1). The expression of GUSB (external control) was used to normalize for variances in input cDNA. For Western blot analysis, 30 μg of protein from total cell extracts or nuclear or cytoplasmic extracts were fractionated in gradient (4-20%) polyacrylamide gels (FMC) and transferred to Hybond-P (Amersham Biosciences) membrane. Lysates were exposed to rabbit polyclonal anti-p16INK4A (Upstate), anti-SUZ12 (Abcam), anti-HOXA9, anti-EZH2, anti-EED or anti-Myc tag (Upstate), followed by horseradish peroxidase-conjugated goat-anti-rabbit antibody (Calbiochem). Actin, tubulin (Sigma), or Lamin B (Santa Cruz Biotechnology) were used as loading controls. RLGS—We carried out RLGS as described (41Hatada I. Hayashizaki Y. Hirotsune S. Komatsubara H. Mukai T. Proc. Natl. Acad. Sci. U. S. A. 1991; 88: 9523-9527Crossref PubMed Scopus (305) Google Scholar). Briefly, nonspecific, sheared ends of genomic DNA (2-5 ug) were blocked in a 10-μl reaction by the addition of nucleotide analogues (αS-dGTP, αS-dCTP, ddATP, ddTTP) with DNA polymerase I (2 units; 37 °C, 20 min) followed by enzyme inactivation (65 °C, 30 min). The buffer was then adjusted and the DNA was digested (37 °C, 2 h) with 20 units NotI (Promega). We used Sequenase (version 2.0, USB) to fill in the NotI ends with [α-32P]dGTP (New England Nuclear) and [α-32P]dCTP (Amersham Biosciences) for 30 min at 37 °C. The labeled DNA was digested (37 °C, 1 h) with EcoRV (20 units; Promega) and a proportion was electrophoresed through a 60-cm long, 0.8% agarose tube gel (first dimension separation). The agarose gel was then equilibrated in HinfI digestion buffer and the DNA digested in the gel with HinfI (700 units; Promega) at 37 °C for 2 h. The agarose gel was then placed horizontally (rotated 90° relative to the first electrophoresis) across the top of a non-denaturing 5% polyacrylamide gel, the two gels connected with molten agarose and the DNA was electrophoresed in the second dimension. The gels were dried and exposed to x-ray film in the presence of intensifying screens (Quanta III, DuPont) for 2-10 days. The central portion of the RLGS profile (grid sections 2A through 5E) exhibits the best fragment resolution and was used for methylation analysis. Of greater than 1000 fragments in this region, 762 which were non-overlapping with other fragments, single copy intensity and present on HMECs from three different individuals were included in the analysis. Of these 762 fragments, 24 showed complete or near complete absence in at least one vHMEC population. To test for the presence of heterogeneity in methylation frequencies among islands, we compared methylation frequencies of the islands to what would be expected under null hypotheses of no preferential methylation sites. To avoid making parametric assumptions, a permutation approach was employed. To test for equal methylation frequency among the islands, we emulated the null hypothesis by fixing the marginal number of methylation events for each clone and permuting methylation events, thus randomly assigning methylation events occurring in a given clone to the islands. For each iteration, the proportion of resulting methylation frequency for each island was retained. The procedure was repeated 10,000 times. Unadjusted p values were assigned by calculating the proportion of permutations in which the resulting methylation frequency for a given island exceeded the observed frequency. Under null hypothesis, the p values should follow a Uniform (0, 1) distribution. We used a one-sample Kolmogorov-Smirnov test to assess the degree of plausibility for the null hypothesis of no differential methylation and obtained a p value of 0. After Bonferroni adjustment for 762 tests, 16 islands were significantly hypermethylated (p value = 0 with upper boundary of 0.0762 because of the limit of 10,000 permutations). Alternatively, by considering maximum frequency observed in each permutation and comparing the observed frequencies to the distribution of the maximum, we obtained a maxT adjusted p value for each island (42Westfall P.H. Young S.S. Resampling-based Multiple Testing: Examples and Methods for p-value Adjustment. Wiley, New York1993Google Scholar). Sixteen islands were assigned maxT adjusted p value less than 0.01. This insures the probability of less than 1% of having at least one false positive. All calculations were performed in a freely available R statistical environment (43Ithaka R. Gentleman R.J. J. Comp. Graph Stat. 1996; 5: 299-314Google Scholar). Bioinformatics programs were used to find the position of RLGS fragments in the genome. Luciferase Reporter Assays—1 × 105 vHMEC were seeded in 24-well plates. After 24 h of treatment with 5-aza-2′-deoxycytidine (1 μm), 1 μg of the promoter reporter (pGL3, EphB4, EphB4mt) was transfected into vHMEC using a cationic lipid (Invitrogen). Lysates were harvested 48 h later and dual luciferase analysis performed (Promega). Equal amounts of CMV-driven constructs were transfected in each experiment, and cotransfection of a Renilla luciferase reporter (20 ng) was used to allow standardization for transfection efficiency. Drug-containing media was replaced every 24 h. All experiments were performed in triplicate. Chromatin Immunoprecipitation—For chromatin immunoprecipitations, DNA-protein cross-linking was performed as described (44Meluh P.B. Broach J.R. Methods Enzymol. 1999; 304: 414-430Crossref PubMed Scopus (47) Google Scholar) with slight modifications. Cells were incubated with 0.5 mm DSG (Pierce) at room temperature for 30 min, then formaldehyde was added to a final concentration of 1%, and cells were incubated at room temperature for 10 min. DNA shearing was performed in nuclei lysis buffer (1% SDS, 10 mm EDTA, 50 mm Tris, pH 8.0, 1× protease inhibitor mixture, Roche) with sonication to achieve an average DNA length of 400-500 bp. Samples were diluted to a final concentration of 0.1% SDS and incubated overnight at 4 °C with 2 μg of either rabbit polyclonal anti-SUZ12 (Abcam), anti-DNMT3a (Novus), anti-DNMT3b (Abcam), anti-DNMT1 (Immgenex), anti-histone H3 (Upstate), or rabbit IgG (mock IP). Samples were incubated with protein A/G-agarose and bound complexes were eluted with 1% SDS, 0.1 m NaHCO3. Samples were incubated 4 h at 65°C to reverse cross-linking, and proteins were digested with Proteinase K. Following purification of DNA fragments (QiaQuick PCR purification kit, Qiagen), promoter sequences were amplified using PCR. The following primer set was used: MR2 nt 42764-42556 of AC004080. Immunohistochemistry—Five-micron sections cut from formalin-fixed paraffin-embedded tissue blocks or tissue arrays (Biogenex) were deparaffinized and rehydrated following standard protocols. Sections were incubated with antisera against HOXA9 (Upstate) following the manufacturer's instructions. Antigen-antibody complexes were visualized using the Vectastain Elite avidin-biotin complex kit following standard protocol (Vector Laboratories). Sections were counterstained in hematoxylin dehydrated through graded alcohols, cleared in xylene, and mounted in permount. Loss of p16INK4A Activity Up-regulates Selected PcG Proteins—Because cells with loss of p16INK4A activity exhibit increased E2F activity, a known regulator of PcG expression, we wished to use microarray analysis to determine if factors involved in epigenetic silencing show altered expression in vHMEC compared with HMEC. Two members of the polycomb group family of proteins, SUZ12 and EZH2, were among the genes that were up-regulated when vHMEC were analyzed by microarray. To verify the gene expression profiling data, we assessed the mRNA levels of several PRC2 genes (SUZ12, EZH2, and EED) in HMEC and vHMEC populations using quantitative real-time PCR. Both SUZ12 and EZH2 mRNA is increased in vHMEC compared with HMEC, 4-fold and 9-fold, respectively (Fig. 1A). These striking differences in PRC gene expression are independent of proliferative differences between HMEC and vHMEC, because both cell populations double with similar kinetics (30 h and 26 h, respectively) and exhibit a similar S phase fraction under the conditions of these analyses (15 and 20%, respectively; data not shown). Additionally the increase in expression of EZH2 and SUZ12 is also observed after normalization of expression to PCNA levels (supplemental Fig. S1A). The levels of a third component of the PRC2 complex, EED, shown to be an E2F target gene in some cell types (5Bracken A.P. Pasini D. Capra M. Prosperini E. Colli E. Helin K. EMBO J. 2003; 22: 5323-5335Crossref PubMed Scopus (972) Google Scholar), remain unchanged. We verified that the up-regulation of SUZ12 and EZH2 mRNAs was indeed accompanied by an increase in protein expression via Western blot analysis (Fig. 1, A and B) and documented that EZH2 localized to the nuclear compartment, while SUZ12 was localized to both the nuclear and cytoplasmic compartment in vHMEC (supplemental Fig. S1B). SUZ12 and EZH2 protein expression is low in HMEC but is increased significantly in vHMEC, whereas the levels of EED remain unchanged (Fig. 1B). HMEC obtained from nine different individuals all display a low level of EZH2 when compared with their isogenic vHMEC population. The basal levels of EZH2 expression in HMEC vary between individuals and extremes of expression are shown in Fig. 1, B and C. To determine if there is a causal relationship between loss of p16INK4A activity and increased expression of PcG genes in these primary human cells, we assessed lysates from HMEC after infection with retrovirus containing a small hairpin RNA (shRNA) to either GFP or p16INK4A by Western blot analysis. Whereas HMEC infected with retrovirus containing a shRNA to GFP (shGFP) have low levels of SUZ12 and EZH2, HMEC infected with retrovirus containing a shRNA to p16INK4A (shp16) show high levels of EZH2 and SUZ12 expression upon decreased p16INK4A levels (Fig. 1C), comparable to the levels of EZH2 and SUZ12 seen in vHMEC (Fig. 1, B and C). To determine whether p16INK4A expression is sufficient to repress PcG protein expression in vHMEC, we assessed lysates from vHMEC after infection with retrovirus containing empty vector control or wild-type p16INK4A by Western blot analysis. We find vHMEC infected with retrovirus containing wild-type p16INK4A have decreased expression of both SUZ12 and EZH2 when compared with vHMEC infected with retrovirus containing empty vector (Fig. 1C). These determinations were made at a time point when vHMEC expressing wild-type p16INK4A were still engaged in the cell cycle (4 days), a time prior to the eventual proliferative arrest that they enter at day 7. Other CDK inhibitors at the CDKN2 locus, p14ARF and p15, are expressed in both HMEC and vHMEC ((33Romanov S.R. Kozakiewicz B.K. Holst C.R. Stampfer M.R. Haupt L.M. Tlsty T.D. Nature. 2001; 409: 633-637Crossref PubMed Scopus (398) Google Scholar) and data not shown). We also assessed the expression of PcG proteins in human mammary fibroblasts (HMF). There is no expression of SUZ12 and EZH2 in HMF (Fig. 1C, parent). Furthermore, expression of PcG proteins cannot be induced in HMF infected with retrovirus containing shp16 (Fig. 1C), demonstrating that loss of p16INK4A activity is sufficient to drive overexpression of SUZ12 and EZH2 in mammary epithelial cells but not human mammary fibroblasts. Taken together, our results demonstrate that, in HMEC, expression of both SUZ12 and EZH2 can be directly influenced by loss of p16INK4A activity in a manner that is independent of proliferation status. Increased Expression of Selected PcG Proteins Is Accompanied by Targeted DNA Hypermethylation—To determine whether p16INK4A-mediated up-regulation of PcG proteins is associated with DNA hypermethylation, we compared the methylation profiles of populations of primary human mammary cells using RLGS, a technique that allows the unbiased screening of genome-wide CpG island methylation events (45Costello J.F. Fruhwald M.C. Smiraglia D.J. Rush L.J. Robertson G.P. Gao X. Wright F.A. Feramisco J.D. Peltomaki P. Lang J.C. Schuller D.E. Yu L. Bloomfield C.D. Caligiuri M.A. Yates A. Nishikawa R. Su Huang H. Petrelli N.J. Zhang X. O'Dorisio M.S. Held W.A. Cavenee W.K. Plass C. Nat. Genet. 2000; 24: 132-138Crossref PubMed Scopus (1167) Google Scholar). We compared in vivo uncultured breast tissue and organoids, as well as in vitro cultured primary cells (HMEC and HMF) to vHMEC that exhibited overexpressed PcG proteins. The uncultured breast tissue, obtained by biopsy, and the paired organoid sample, partially processed to remove most stromal components and enriched in fibroblasts and epithelial cells, retain the epithelial cells in their physiological environment and allow us to detect potential culture effects. We p